An overview of community livelihoods in Biosphere Reserves: based on the sustainable livelihoods framework for the 21st century - Yang, Lun (Frontiers in Forests and Global Change, 2024)
Biosphere Reserves (BRs) are the protected areas proposed by the Man and the Biosphere Programme for harmonious coexistence between humanity and nature. Human activities represented by community livelihoods have always been one of the critical issues in the protection and development of BRs. However, the lack of comprehensive research on the status quo and problems of community livelihoods in BRs has caused difficulties in policy formulation and management. In the form of a literature review, this study attempts to summarize and sort out the overview of community livelihoods in BRs by screening the academic literature with the keywords of BRs and livelihoods and using the 21st Century Sustainable Livelihood Framework as the road map. As a result, community livelihoods in BRs highly depend on environmental resources, increasing vulnerability. Although establishing BRs has brought financial and business opportunities to the community, it also provides environmental resources, public services, and geographical areas in the climate-environmental context needed for livelihood maintenance. However, community livelihoods and climate-environmental context show a contradictory relationship of ‘mismatch between supply and demand’ in environmental resources and public services in BRs. In geographical areas, the conflicts brought by illegal activities, invasive alien species, and wildlife-human conflicts are also gradually increasing. At the same time, unbalanced physical and financial assets and relational power with mixed praise also challenge the sustainable development of community livelihoods in BRs. Therefore, this study believes that through multi-stakeholder joint efforts, BRs Friendly Community Livelihoods other than the initial livelihood with high environmental resource dependence can be sought for communities through livelihood diversification, community participatory management, and community spatial pattern refinement.